Analisis Sistem Inventaris IT menggunakan Prototype dan ISO 25010 pada PT Snapdev Digital Indonesia - Achmad Fadli; Aditya Widhi Saputro; Chairul Anwar (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
The development of information technology encourages companies to improve the effectiveness of integrated IT asset and inventory management. PT Snapdev Digital Indonesia, as a company operating in the technology sector, still faces several challenges in managing IT inventory, such as unstructured device recording, less optimal asset monitoring processes, and delays in handling helpdesk tickets. This study aims to design and analyze a web-based IT inventory system using the Agile method and prototype approach, as well as to evaluate the system quality based on the ISO/IEC 25010 standard. The system was developed using UML modeling consisting of use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The implementation of the system was carried out through a website-based platform with features including inventory management, helpdesk tickets, ticket monitoring, knowledge base, technician scheduling, and system reporting. System testing was conducted using the ISO/IEC 25010 standard focusing on the aspects of functional suitability, usability, reliability, performance efficiency, and security. The results of this study indicate that the developed system is capable of improving the effectiveness of IT inventory management, accelerating the helpdesk ticket handling process, and assisting the company in generating inventory reports more quickly and accurately.